Prof dr FJ van Zyl se Skrifbeskouing - P. A. Geyser (HTS Teologiese Studies/Theological Studies, 1989)
Prof Dr FJ van Zyl’s view on Scripture In this article an endeavour is made to depict a representive picture of Professor Van Zyl’s many articles about his view on Scripture. As a theologian of the Reformed tradition he was one of a very selected few who articulated a theological reflection about Scripture. Moving from Karl Barth’s viewpoint, he developed his own ideas while also paving the way for historical criticism and other modern methods of research into the understanding of the Bible as such.